EXERGETIC AND ECONOMIC ANALYSIS OF SUBCOOLING & SUPERHEATING EFFECT ON VAPOR COMPRESSION REFRIGERATION SYSTEM - Karakurt, A. Sinan; Gunes, Umit; Ust, Yasin (AMER SOC MECHANICAL ENGINEERS, 2016)
Refrigeration systems are one of the most common and the oldest thermodynamic system that almost equal to human history. Exergetic and economic effects of subcooling & superheating on vapor compression refrigeration system are analyzed and examined in terms of different refrigerants, working conditions (temperature and pressures), condenser and evaporator effectiveness and temperatures and isentropic efficiency of compressor behalf of coefficient of performance, exergetic efficiency, exergetic performance coefficient and ecological coefficient of performance. The results show that variations of the condenser and evaporator temperatures, pressure losses in heat exchangers and isentropic efficiency of compressor are highly related to performance and economic parameters such as heat exchange areas and power consumption for subcooling & superheating refrigeration system (SSRS).
Keywords: PERFORMANCE; COEFFICIENT; CYCLE; Energy & Fuels; Engineering